In this problem, it is given that the logarithm of a quadratic expression $x$ square minus $2$ times $x$ plus $65$ to base $5$ minus $x$ is equal to $2$.

$\log_{5-x}{(x^2-2x+65)}$ $\,=\,$ $2$

Now, let’s learn how to solve this logarithmic equation to solve the value of $x$.

It is essential to release the equation from the logarithmic form for solving the given logarithmic equation. So, use the mathematical relation between the exponents and logarithms for converting the logarithmic equation into exponential equation.

$\implies$ $x^2-2x+65$ $\,=\,$ $(5-x)^2$

On the right hand side of the equation, there is an expression and it is the square of $5$ minus $x$. The $5$ minus $x$ whole square can be expanded as per the square of difference formula.

$\implies$ $x^2$ $-$ $2x$ $+$ $65$ $\,=\,$ $5^2$ $+$ $x^2$ $-$ $2 \times 5 \times x$

There is a quadratic expression on both sides of the equation. Move the expression on one side to other side for solving the equation by simplification.

$\implies$ $x^2$ $-$ $2x$ $+$ $65$ $\,=\,$ $25$ $+$ $x^2$ $-$ $10x$

$\implies$ $x^2$ $-$ $2x$ $+$ $65$ $-$ $x^2$ $+$ $10x$ $-$ $25$ $\,=\,$ $0$

$\implies$ $x^2$ $-$ $x^2$ $+$ $10x$ $-$ $2x$ $+$ $65$ $-$ $25$ $\,=\,$ $0$

Cancel the equal terms, add the like terms and finally subtract the numbers to complete the simplification of the expression on the left hand side of the equation.

$\implies$ $\cancel{x^2}$ $-$ $\cancel{x^2}$ $+$ $8x$ $+$ $40$ $\,=\,$ $0$

The given logarithmic equation is successfully simplified as a linear equation in one variable.

$\implies$ $8x$ $+$ $40$ $\,=\,$ $0$

Now, solve the linear equation in one variable to get the value of the variable $x$.

$\implies$ $8x$ $\,=\,$ $-40$

$\implies$ $x$ $\,=\,$ $\dfrac{-40}{8}$

$\implies$ $x$ $\,=\,$ $-\dfrac{40}{8}$

$\implies$ $x$ $\,=\,$ $-\dfrac{\cancel{40}}{\cancel{8}}$

$\,\,\,\therefore\,\,\,\,\,\,$ $x$ $\,=\,$ $-5$

In this problem, $\log_{5-x}{(x^2-2x+65)}$ $\,=\,$ $2$ is the given log equation and it is solved that $x = -5$. Now, substitute the value of $x$ on the left hand side of the equation.

$=\,\,\,$ $\log_{5-(-5)}{\big((-5)^2-2(-5)+65\big)}$

$=\,\,\,$ $\log_{10}{(25+10+65)}$

$=\,\,\,$ $\log_{10}{(100)}$

$=\,\,\,$ $\log_{10}{\big(10^2\big)}$

$=\,\,\,$ $2 \times \log_{10}{(10)}$

$=\,\,\,$ $2 \times 1$

$=\,\,\,$ $2$

It is evaluated that the value of $\log_{5-x}{(x^2-2x+65)}$ is equal to $2$ when the value of $x$ is equal to $-5$.

Latest Math Topics

Latest Math Problems

A best free mathematics education website for students, teachers and researchers.

Learn each topic of the mathematics easily with understandable proofs and visual animation graphics.

Learn how to solve the maths problems in different methods with understandable steps.

Copyright © 2012 - 2021 Math Doubts, All Rights Reserved